PERSEPSI VARIASI MENGAJAR GURU DAN PEMANFAATAN MUSEUM TRINIL TERHADAP MINAT BELAJAR SEJARAH SISWA KELAS X SMA NEGERI 1 KEDUNGGALAR NGAWI TAHUN AJARAN 2012/2013 - Nurhidayati, Ervina (Candi, 2013)
Perception about teacher?s teaching variation and the utilization of museums trinil to the history learning interest of 10th grade students of SMA N 1 Kedunggalar. The purpose of this research is to know the correlation between: (1) perception about teacher?s teaching variation to to the history learning interest; (2) the utilization of museums trinil to the history learning interest; (3) Perception about teacher?s teaching variation and the utilization of museums trinil to the history learning interest. This research used quantitative method with survey approach and descriptive analysis method. The samples of research are 51 students from 2 classes of SMAN 1 Kedunggalar. In taking of the samples used sample random sampling techniques from 221 students in population. The data were collected by using questionnaire in the form of likert scale. The techniques of data analysis were correlation and double analysis regression techniques. The research show that perception about teacher?s teaching variation and the history learning interest have positive and significant correlation. it is proved with the result of calculation ro > rt or 0,551 > 0,279 and the value of t > t table or 4,627 > 1,684. The utilization of museums trinil and the history learning interest have positive and significant correlation. it is proved with the result of calculation ro > rt or 0,558 > 0,279 and the value of t > t table or 4,708 >1,684. Perception about teacher?s teaching variation and the utilization of museums trinil with the history learning interest in together have positive and significant correlation. it is proved with the result of calculation ro > rt or 0,681 > 0,279 with the probability of 0,000 < 0,05. The significance of the F test with db = 2 opponents 48, the obtained Fht > Ft or 20.766> 3.19 and the regression Y = -2.367 + 0.530 X1 + 0.493 X2. Keyword: teaching variation, utilization of museums, students perception